Bioelectric cues from piezoelectric materials in stem-cell adhesion and migration - Chen, Ning; Su, Yangyang; Zhao, Renliang; Deng, Xiangtian (Frontiers in Cell and Developmental Biology, 2025)
Stem cell adhesion and migration are fundamental processes in tissue regeneration and repair; however, their efficiency in vivo is often limited by the complexity of the microenvironment. Endogenous bioelectrical cues, such as electric fields present during development and wound healing, play a critical role in guiding these cellular behaviors. Piezoelectric biomaterials, which can convert mechanical stimuli into electrical signals, have recently emerged as promising platforms for recapitulating these bioelectric cues without the need for external power sources. In this mini-review, we summarize the recent advances in the use of piezoelectric scaffolds to modulate stem cell adhesion and migration. We highlight the underlying mechanisms, including integrin/focal adhesion kinase activation, calcium signaling, and electrotaxis, which mediate enhanced adhesion, focal adhesion maturation, and directed cell migration. Representative applications in bone, cartilage, nerve, and muscle tissue engineering are discussed, with an emphasis on how piezoelectric scaffolds improve regeneration by providing dynamic and self-sustained electrical stimulation. Finally, we outline the major challenges, such as balancing piezoelectric output with biocompatibility, controlling in vivo stimulation parameters, and elucidating precise sensing mechanisms, and propose future directions for clinical translation. By integrating insights from materials science, mechanobiology, and regenerative medicine, piezoelectric biomaterials hold strong potential as next-generation smart scaffolds for orchestrating stem cell behavior and accelerating functional tissue repair.